Nuclear structure studies in mirror nuclei. (1st March 2023) - Tonev, D.; de Angelis, G.; Deloncle, I.; Goutev, N.; De Gregorio, G.; Pantaleev, I. L.; Demerdjiev, A.; Geleva, E.; Dimitrov, D. T.; Genchev, S. G.; Lakov, N.; Lalev, V. L.; et al.
Abstract: The nuclear structure of the A=31 and A=47 mirror couples produced by two fusion evaporation reactions has been elaborated, utilizing the Doppler-shift attenuation method. Excited states in 31 P and 31 S were populated using the 1p and 1n exit channels, respectively, of the reaction 20 Ne + 12 C, while in 47 Cr and 47 V couple excited states were populated based on 28 Si + 28 Si reaction, as products of 2αn and 2αp exit channels. The A=31 mirror couple was studied utilizing Piave-Alpi accelerator of the Laboratori Nazionali di Legnaro with GASP multidetector array and for A=47 one - with the EUROBALL array using XTU Tandem also in Legnaro. In both cases the lifetime measurements in mirror couples at the same experiment open possibilities for investigations of isospin symmetry. Determined B(E1) strengths in the mirror nuclei 31 P and 31 S allow to extract the isoscalar component, which can reach up to 24% of the isovector one. The B(E1) values can be modeled by the Equation of motion method. In the case of A=47 mirror couple, the quadrupole moments can be described by shell-model calculations.